Integration of theoretical and clinical disciplines teaching as one of factors of medical knowledge efficacy - Vastyanov, R. S.; Stoyanov, A. N.; Dzygal, A. F.; Savytskyi, i. V.; Demidov, V. M.; Levchenko, Ye. M.; Onufrienko, O. V.; Ostapenko, I. O. (Journal of Education, Health and Sport, 2017)
The article discusses the problem of medical students theoretical knowledge improvement that will significantly improve their clinical knowledge. The main factors that determine medical students’ positive motivation to study are considered. The authors prove that both theoretical and clinical disciplines teaching integration is possible as a result of complex approach to students teaching that will result in students’ knowledge survival on the higher courses. Leading role belongs to the theoretical departments which workers by writing textbooks and manuals, creating teaching multimedia programmes, using exact control and students' knowledge evaluation will provide the necessary motivational component of students’ further teaching on clinical departments. The integrated approach contributes to future profession single picture formation, motivates students to theoretical and clinical disciplines deep study. The future doctors teaching process reforming at Odessa National Medical University General and Clinical Pathological Physiology Department is given as an example. Authors guesses that new methodical methods of working with students in the practical work introduction, the change in the technology of teaching, the modification of the educational process, the approximation of theoretical knowledge to the patient's bed, the greater students interest in the positive end-goal - a correct diagnosis and cure of the patient - will allow to optimize the educational process and improve the quality of students’ training.